Heavy metal contents in the most productive Argentinean Humid Pampa soils. (28th June 2019) - Bilos, Claudio; Tatone, Leandro Martin; Skorupka, Carlos Norberto; Astoviza, Malena Julia; Romero, Camila Lucia; Colombo, Juan Carlos
Argentinean Humid Pampa topsoil samples from sites with different land use patterns were analysed. Texture was dominated by fines (silt+clay > 50%) with high total organic carbon content (2.8 ± 1.8%), particularly in finer soils (3.7-9.9% to 0.99% in sandy soils). Carbon:nitrogen relationship was relatively homogeneous (13.9 ± 3.6%) pointing to a dominant contribution of terrestrial plant detritus. Heavy metal concentrations were low (Fe: 1.77 ± 0.50%; Mn: 446 ± 171; Zn: 48.4 ± 19.5; Cu: 17.6 ± 6.0; Pb: 10.0 ± 4.8; Cr: 7.2 ± 1.8; Ni: 6.1 ± 1.7; Cd: 0.05 ± 0.03 µg g -1 ) and spatially homogeneous (<50%) with more variability for Cd (±58%); the exception was an industrial site with atypically high values for Zn (111 µg g -1 ) and Cr (11.9 µg g -1 ). Heavy metal levels were lower than the Soil Environmental Quality Guidelines for Agriculture land use established in international legislation. Mn-Cu-Pb-Ni-Cd-Cr exhibited positive correlations with soil fine contents (R 2 Mn = 0.76; R 2 Cu = 0.73; R 2 Pb = 0.73; R 2 Ni = 0.56; R 2 Cd = 0.45; R 2 Cr = 0.38; p > 0.05). Heavy metal enrichment factors were low (0.07-2.28) indicating a natural origin.